Thermal conductivity of TiO2 nanotube: a molecular dynamics study. (19th December 2018) - Yang, Liang; Wang, Cai-Zhuang; Lin, Shiwei; Chen, Taohai; Cao, Yang; Zhang, Ping; Liu, Xiaoheng
Abstract: The thermal conductivity of anatase TiO2 nanotubes was investigated using equilibrium molecular dynamics simulations based on Green-Kubo formalism. The calculated thermal conductivity of for anatase crystal at room temperature agrees well with experimental value of ~8.5 W K −1 · m −1, demonstrating that the method used in our calculation can provide a good description for the thermal transport of TiO2 . The dependence of the thermal conductivity of TiO2 nanotubes with temperature, tube size and chirality were studied in detail. The relationship between the thermal conductivity and the vibrational density-of-states of the nanotubes was also investigated.